One-Year Consumption of a Mediterranean-Like Dietary Pattern With Vitamin D3 Supplements Induced Small Scale but Extensive Changes of Immune Cell Phenotype, Co-receptor Expression and Innate Immune Responses in Healthy Elderly Subjects: Results From the United Kingdom Arm of the NU-AGE Trial - Maijo, Monica; Ivory, Kamal; Clements, Sarah J.; Dainty, Jack R.; Jennings, Amy; Gillings, Rachel; Fairweather-Tait, Susan; Gulisano, Massimo; Santoro, Aurelia; Franceschi, Claudio; Carding, Simon R.; Nicoletti, Claudio (Frontiers in Physiology, 2018)
Amongst the major features of ageing are chronic low grade inflammation and a decline in immune function. The Mediterranean diet (MD) is considered to be a valuable tool to improve health status, and although beneficial effects have been reported, to date, immunological outcomes have not been extensively studied. We aimed to test the hypothesis that one year of an tailored intervention based on the MD would improve innate immune responses in healthy elderly subjects (65–79 y) from the English cohort (272 subjects recruited) of the NU-AGE randomized, controlled study (clinicaltrials.gov, NCT01754012). Of the 272 subjects forming the UK cohort a subgroup of 122 subjects (61 from the intervention group and 61 from the control group) was used to evaluate ex-vivo innate immune response, phenotype of circulating immune cells, and levels of pro- and anti-inflammatory markers. Odds Ratio (OR) was calculated for all the parameters analysed. After adjustment by gender, MD-females with a BMI<31 kg/m2 had a significant upregulation of circulating CD40+CD86+ cells (OR 3.44, 95% CI 1.01-11.75, P=0.0437). Furthermore, in all MD subjects, regardless of gender, we observed a MD-dependent changes, although not statistically significant of immune-critical parameters including T cell degranulation, cytokine production and co-receptor expression. Overall, our study showed that adherence to an individually tailored Mediterranean-like dietary pattern with vitamin D3 (10 µg/day) supplements for one year modified a large variety of parameters of immune function in healthy, elderly subjects. We interpreted these data as showing that the MD in later life could improve aspects of innate immunity and thus it could aid the design of strategies to counteract age-associated disturbances associated with our ageing population.